Spending More or Spending Better : Improving Education Financing in Indonesia, Extended Executive Summary - World Bank (World Bank, Jakarta, 2013)
Indonesia is the world's fourth most populous country, with more than 238 million people living in an archipelago comprising over 17,000 islands. Over the past decade the Indonesian economy has experienced positive economic growth, reduced poverty, and made continued progress towards many of the Millennium Development Goals (MDGs). For example, Indonesia has already met and surpassed projected reductions in the number of underweight children under five years old to below 18 percent and is on track to meeting its targets for reducing overall child mortality and the targets for achieving universal basic education. While clear progress has been made on reducing poverty rates, inequality has persisted, with the result that many children and families have not shared in these gains. Over 30 million Indonesians live below the poverty line (US $2 per day) and half of all households are clustered around the poverty line. Of the poor, 65 percent currently live in rural areas. For these families, national economic improvements have brought only modest gains in health and education, putting children's development at risk and threatening national progress. A notable achievement for Indonesia is that primary school enrollment is now near 100 percent for boys and girls of all income levels. However, as children move through the primary years, the enrollment disparities seen in Early Childhood Education and Development, or ECED services re-emerge. Educational attainment profiles reveal that while almost all children from all segments of society start primary school, children from poorer households and children from rural areas have more difficulties progressing from lower levels of education to higher levels. Only 55 percent of rural children make it to junior secondary school, and less than a quarter enroll in senior secondary. In contrast, 80 percent of urban children make it to junior secondary school and almost two-thirds enroll in senior secondary.